Dilute carbon in H3S under pressure - Xiaoyu Wang; Tiange Bi; Katerina P. Hilleke; Anmol Lamichhane; Russell J. Hemley; Eva Zurek (npj Computational Materials)
Abstract Recently, room temperature superconductivity was measured in a carbonaceous sulfur hydride material whose identity remains unknown. Herein, first-principles calculations are performed to provide a chemical basis for structural candidates derived by doping H3S with low levels of carbon. Pressure stabilizes unusual bonding configurations about the carbon atoms, which can be six-fold coordinated as CH6 entities within the cubic H3S framework, or four-fold coordinated as methane intercalated into the H-S lattice, with or without an additional hydrogen in the framework. The doping breaks degenerate bands, lowering the density of states at the Fermi level (N F), and localizing electrons in C-H bonds. Low levels of CH4 doping do not increase N F to values as high as those calculated for $$Im\bar{3}m$$ I m 3 ¯ m -H3S, but they can yield a larger logarithmic average phonon frequency, and an electron–phonon coupling parameter comparable to that of R3m-H3S. The implications of carbon doping on the superconducting properties are discussed.